Women and Heart Disease: Knowledge Differences between Primary Care and Speciality Practices - Reilly, Helene (My University, 2015)
Problem Statement: Cardiovascular disease (CVD) is the leading cause of death in the United States for women and the second leading cause of death in Pitt County North Carolina. Evidence in the literature supports diminished awareness of heart disease among women and limited data as to provider knowledge of the current guidelines for the prevention of CVD in women. Purpose: This Doctor of Nursing (DNP) project examined the differences in knowledge, barriers, and practice of the 2011 Guidelines for the Prevention of CVD in Women by administering a survey to healthcare providers (HCPs) in primary care and selected specialty practices at a rural Southeastern US university clinic setting. Questions: (1) Is there a difference in knowledge of women and heart disease between primary care, cardiology, and OB/GYN practices? (2) What are the barriers affecting the provision of CVD risk therapies in women? (3) Is there a difference in the practice of women and heart disease between primary care, cardiology, and OB/GYN practices? Methods: Self-administered web-based anonymous questionnaire with a convenience sample of 147 Advanced Practice Registered Nurses, Physician Assistants, and Physicians in specialty and primary care settings. Analysis: Descriptive statistical analysis calculated by Statistical Package for the Social Sciences® (SPSS) using frequencies and percentages, and cross-tabulation to compare variables with practice site and HCP type. Waist circumference measurement and depression screening was performed less than half the time. Significance: Education of HCPs on the current guidelines and implementation into electronic health record.
Keywords: Women; Cardiovascular Diseases; Healthcare providers; Knowledge; Awareness